Strategies for limited and deficit irrigation to maximize on-farm profit potential in Colorado's South Platte Basin - Smith, Stephen W., author; Grigg, Neil S., advisor; Loftis, Jim, committee member; Pritchett, James G., committee member; Wilkins, John, committee member (Colorado State University. Libraries, 2011)
Municipalities and other water providers are expected to seek increasing amounts of agricultural water to meet the demand to be created by projected future growth along the Front Range of Colorado and within the South Platte Basin. Farms often are acquired outright, the water rights parted off, and the decree changed to municipal use--a process commonly referred to in the regional water community as "buy and dry". Concerned about the negative effects of buy and dry on agriculture, rural communities, and even the environment, the State of Colorado has funded research into alternative, less permanent methods for transferring water from agriculture. The purpose of this dissertation is to demonstrate through a simulation and optimization model that successful farming operations can be continued while agricultural producers benefit financially from a proportional parting-off of the water right. . Further, this dissertation will describe what an implementation embodiment of the technology described looks like operationally and as a practical matter. Colorado water law allows transfer of only that portion of the water right which is used by the crop--its "consumptive use" (CU). Once the historic CU is established and adjudicated through Colorado's Water Court, the CU for that water right becomes a known quantity, thus allowing for comprehensive consideration as to how that CU water might be used to the owner's economic advantage. Specifically, a future water use might be to continue farming but to lease or sell a proportion of the quantified CU water to a higher economic use - likely municipal or environmental interests. This dissertation presents factors associated with the use of, and change in, water rights that may be considered by farmers interested in evaluating a package of changed farming practices intended to optimize future revenues. A future low-risk revenue stream may be brought into the farm's revenue forecast by virtue of the lease of a proportional amount of water to a municipal, industrial, or environmental user. Optimization algorithms are used to evaluate a farmer-considered package of changed practices which may include: deficit irrigation, new crops, dryland crops, permanent or rotational fallowing of fields, and crop rotations. Some farmers will also consider upgraded irrigation systems as an aspect of implementing these practices. The farmer-driven optimization may include any or all of these changed practices as well as continued full irrigation of crops. To evaluate and compare multiple practices as a cohesive package and in the context of the option to lease water is new. The simulation and optimization model output assists in comparing historic practices and net returns with future practices and net returns which would include a revenue stream associated with a lease or sale of a proportion of the farmer's CU water. The actual comparison between alternatives is accomplished by evaluating the change in net returns between historic practices and modeled future practices. The model utilizes crop water production functions, some of which are very newly researched and reported, to forecast crop yields based on deficit irrigation practices. The model can utilize up to 20 fields and 18 combinations of irrigation practices and crops. Up to seven deficit irrigation crops per field can be evaluated within a simulation and optimization scenario. Recommendations are made for future research and software development that will incorporate the optimization routines into a larger collection of data inputs and a database intended to help farmers, ditch companies, or cooperative farmer groups manage their consumptive use water under a change decree and aggregated changed practices. It is recommended that the ultimate and fully implemented system include: * A package of technologies under one umbrella software program. * A decision support system (DSS). * A farm operations simulation. * An optimization program for year-to-year evaluation of alternative farm operational strategies and potential for changed practices. * A tool for evaluating a proportional parting off of consumptive use water. * A means of developing and monitoring an annual water use budget. * A database for cataloging historical and current operations of substitute water supply plans or change case decrees. * A monitoring and reporting system for documenting the implementation strategy. * A planning tool used year after year to plan pending annual operations against a farm or farmer cooperative total entity water budget. Primary issues and pitfalls to implementing the process and strategies described are framed by these questions: 1. Can municipal interests view a long term lease as a viable part of their water portfolio and their projected safe yield at a future date? 2. Can farmers accept the perceived dramatic changes to their farming operations? 3. Can the science underpin the strategy sufficiently to satisfy change case objectors and the Colorado Water Court? 4. Can water be physically transferred based on existing water diversion and delivery infrastructure or is new infrastructure required in some cases? 5. Will farmers be interested in and accepting of a long term lease and might they also consider a buyout of the lease at a discounted net present worth? 6. Do existing State of Colorado statutes support the type of water transfer that is described?
Keywords: farming practices; mathematical optimization; irrigation engineering; consumptive use; expert system; water rights quantification